Potential Therapeutic and Health Benefits of Spirulina Microalgae, in Neurodegenerative Disorders: From Nutraceutical to Neuroprotectant - Sharma, Seema; Tanwar, Sampat Singh; Dwivedi, Sumeet; Khan, Sheema (Current Biotechnology, 2025)
Neurodegenerative diseases such as Alzheimer’s disease (AD) and Parkinson’s disease (PD) are progressive disorders marked by neuronal loss, synaptic dysfunction, and cognitive or motor decline. Oxidative stress and chronic neuroinflammation are key drivers in their pathology. In AD, β-amyloid plaques and tau hyperphosphorylation cause mitochondrial damage and ROS overproduction, while PD involves dopaminergic neuronal loss due to oxidative damage. Elevated cytokines like TNF-α, IL-1β, and IL-6 further worsen neuronal injury. Spirulina (Arthrospira platensis), a nutrient-rich cyanobacterium, is gaining attention as a neuroprotective nutraceutical. Its bioactive compounds-C-phycocyanin, β-carotene, tocopherols, and γ-linolenic acid-exhibit strong antioxidant and anti-inflammatory properties. Preclinical studies show spirulina enhances antioxidant enzymes, lowers lipid peroxidation, and improves cognitive performance. This review analyzed preclinical and clinical studies from PubMed, Scopus, and Web of Science focusing on spirulina’s effects in AD and PD models. Spirulina reduced oxidative markers (MDA, NO), increased antioxidant enzymes (GPx, SOD), downregulated pro-apoptotic genes (caspase-3, Bax), and upregulated anti-apoptotic Bcl-2. It also inhibited NF-κB signalling and reduced inflammatory cytokines. A clinical trial in AD patients reported significant MMSE score improvements with spirulina supplementation. Advanced delivery systems like spirulina-loaded nanoparticles and niosomes enhanced its bioavailability and neuroprotective effects in animal models. Overall, spirulina shows promise in mitigating neurodegeneration by targeting oxidative stress and inflammation. Despite encouraging results, larger clinical trials are needed to confirm its therapeutic potential as a safe, effective nutraceutical for neurodegenerative diseases.
Keywords: neuroprotective; inflammation; amyloid beta; antioxidants